Prevalence of induced abortion among Chinese women aged 18–49 years: Findings from three cross-sectional studies - Kang, Liangyu; Liu, Jue; Ma, Qiuyue; Jing, Wenzhan; Wu, Yu; Zhang, Shikun; Liu, Min (Frontiers in Public Health, 2022)
There are few latest researches about induced abortion in China. We aimed to evaluate the prevalence of induced abortion and the related factors, thereby helping make targeted policies and measures to promote women's health. Three comparable cross-sectional surveys among Chinese women aged 18–49 years were performed in 2016, 2017, and 2021. A total of 14,573 eligible respondents were included in the study. 16.70% (95%CI 16.10%-17.31%) of respondents self-reported having experienced induced abortion, while 6.88% (95%CI 6.46%-7.29%) self-reported repeat induced abortion. Age range of 25–49 years (aOR 2.27–6.31, all P<0.05), living in western (aOR 1.72, 95%CI 1.50–1.98) and central (aOR 1.36, 95%CI 1.21–1.52) regions, having children (aOR 2.85, 95%CI 2.35–3.46) were associated with higher prevalence of induced abortion. Moreover, age range of 25–49 years, living in western and central regions, having children were also related to higher prevalence of repeat induced abortion (aOR 1.67–11.52, all P<0.05). Conversely, educational level of college or higher, household annual income over 80,000 Chinese yuan were associated with lower prevalence of induced abortion and repeat induced abortion (aOR 0.52–0.80, all P<0.05). Induced abortion remains noticeable in China. Sustained efforts are required to reduce unintentional pregnancy, improve reproductive health and post-abortion care services, and promote women's health.